1992
DOI: 10.1002/jmri.1880020416
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of fatty liver with MR imaging

Abstract: The diagnosis of fatty liver with magnetic resonance (MR) imaging was evaluated in experimental rat models of simple fatty infiltration and fatty liver with hepatocellular injury. T1 and T2 were measured ex vivo and correlated with the histologic degree of fatty infiltration. Enhancement of fatty liver with four different cells-specific contrast agents was studied with ex vivo relaxometry and in vivo MR imaging. Quantitative analysis of conventional and chemical shift MR images was correlated with biochemicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0
1

Year Published

1994
1994
2008
2008

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 40 publications
(4 reference statements)
1
24
0
1
Order By: Relevance
“…Prolonged T 1water was reported by Hazle et al (8) and Ling and Brauer (30). However, in protein-depleted fatty liver (8) and sucrose/orotic acid-induced fatty liver (19), the T1 value was shortened.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Prolonged T 1water was reported by Hazle et al (8) and Ling and Brauer (30). However, in protein-depleted fatty liver (8) and sucrose/orotic acid-induced fatty liver (19), the T1 value was shortened.…”
Section: Discussionmentioning
confidence: 95%
“…In the past decades, however, many studies have reported the various changes of relaxation times in fatty liver induced by different experimental models (15)(16)(17)(18)(19). By single exponential hypothesis, the statistically significantly shorter T1 relaxation time and longer T2 relaxation time for fat than for water would suggest that the global T1 and T2 found in liver with fatty infiltration would be decreased and increased.…”
Section: Discussionmentioning
confidence: 99%
“…A small number of additional studies (8)(9)(10) have also shown the ability to measure liver fat with T1-weighted MR imaging. By using …”
Section: Discussionmentioning
confidence: 99%
“…Bahl et al rat models of simple fatty infiltration and fatty liver with hepatocellular injury, Kreft et al (8) found that conventional T1-weighted images and chemical shift images showed good correlation (r ϭ 0.83 and 0.80, respectively) between SI and the degree of steatosis, although only chemical shift imaging was reportedly reliable. Qayyum et al (10) demonstrated that liver fat may be quantified with both opposed-phase gradient-echo and fat-suppressed fast spinecho MR imaging (r ϭ 0.69 and 0.92, respectively; P Ͻ .01) in patients without cirrhosis (n ϭ 11).…”
Section: Gastrointestinal Imaging: Liver Steatosis: Mr Imaging Biomarmentioning
confidence: 99%
See 1 more Smart Citation